Community Empowerment Strategy Towards The Problem Of Stunting In Bogak Village - Wasiyem, Wasiyem; Shofwan Hafiz Siregar; Alif Araafi; Muhammad Taufik Hidayat; T. Muhammad Fariz N (Sean Institute, 2024)
Stunting is a chronic nutritional problem that greatly affects children's growth and development, especially in developing countries such as Indonesia. This study highlights the empowerment strategy of the UINSU Medan 97 KKN Group in Bogak Village, Tanjung Tiram, Batu Bara, to overcome stunting. Using a qualitative descriptive approach, the strategies used included nutrition education, supplementary feeding counseling, parental monitoring, and collaboration with local authorities. This intervention resulted in increased knowledge, behavioral changes, and decreased stunting rates. This success shows that student empowerment can effectively address public health problems such as stunting and be applied in similar fields.